PERENCANAAN KOMUNIKASI BANK INDONESIA PROVINSI RIAU DALAM MENSOSIALISASIKAN PROGRAM QRIS QR CODE INDONESIAN STANDARD DI PEKANBARU - Muhammad Resfi Hambali; Yasir " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Bank Indonesia, which presents payment methods using QR Codes, connects payment transaction services with QR Code smartphone cameras that have been connected to user accounts called QRIS QR Code Indonesian Standard. To achieve this goal, of course, communication planning is needed in socializing the QRIS QR Code Indonesian Standard program to the community in order to realize the QRIS QR Code Indonesian Standard program especially in Pekanbaru City. This research uses qualitative methods with a descriptive approach. The research informant numbered fives people using purposive techniques with informants. Data collection techniques are interviews, observations, and documentation. The data analysis technique was performed using Miles and Huberman's interactive data analysis model. To achieve the validity of the data in this study the authors used extension of participation and triangulation.The results of this study show that the target of communication planning in socializing the QRIS QR Code Indonesian Standard program in Pekanbaru consists of five target groups, namely PJSP (Payment System Service Provider), government, merchants, educational institutions and the people of Pekanbaru through channels or communication media. Communication planning in socializing the QRIS QR Code Indonesian Standard program has a message that is informative, persuasive, and educative. But in the implementation of communication planning in socializing the QRIS QR Code Indonesian Standard program has several obstacles that become an evaluation of the socialization program that includes 2 stages.Keywords: QRIS QR Code-Bank Indonesia-Pekanbaru